The Effect of Virtual Laboratories on Improving Students’ SRL: An Umbrella Systematic Review - Amalia Sapriati; Astri Dwi Jayanti Suhandoko; Audi Yundayani; Rafidah Abdul Karim; Udan Kusmawan; Airil Haimi Mohd Adnan; Ardiansyah Azhary Suhandoko (Education Sciences, 2023)
Virtual laboratory (VLab) has been observed for its function for the merit of online course delivery. It is believed that the existence of VLab may enhance students’ academic achievements. However, the study which researches its impact on the students’ independence is still limited. This systematic review study aims to determine students’ self-regulated learning (SRL) on the use of VLab by implementing PICOS (Population, Intervention, Comparison, Outcome, Study Design). Further, we examined whether the strategies of SRL, such as cognitive, metacognitive, motivational, behavioral, and contextual strategies owned by students at higher education levels, increased because of leveraging the VLab. We identified 267 articles from Scopus and the Web of Science databases, then utilized the PRISMA guidelines to specify the 249 eligible articles. As a result, only 20 articles passed the criteria of the feasibility stage (1) higher education level, (2) informing online learning, (3) containing materials discussing VLab, and (4) representing the concept of SRL. However, the finding showed that all interventions had positively affected students’ performance. Based on the analyzed data, we confirm that VLab can be considered for providing the learning experience since it bridges the gap between students’ prior knowledge and experience and provides an active social experience.